Development of Case Study Based Learning Strategy Textbook to Improve Critical Thinking Ability of University Students - Rizka, Mifta; Permatasari, Silvia; Sari, Filma Alia; Isjoni, M.Yogi Riyantama (STAI Hubbulwathan Duri, 2024)
Critical thinking skills are essential to address future challenges. An effective way to improve these skills is through case study-based learning activities. This research aims to develop a specially designed textbook with a case study-based learning strategy to improve students' critical thinking skills. The development process is based on the Borg and Gall model which focuses on the creation of practical educational products. This research was conducted at the Economic Education Research Program, Faculty of Teacher Training and Education, Riau University. This research method follows the 4-D development model by Thiagarajan, Dorothy S. Semmel and Melvin I. Semmel. It includes four phases: definition, design, development, and dissemination. First, the need for a textbook based on the case study was assessed. Then a detailed and systematic design was made and the first product was compiled and validated through expert testing involving FETT material, media and language experts from Riau University. Through the verification process, the textbook was classified as a good textbook and suitable for use. The textbooks were distributed to instructors and practiced in class. This development produces practical and quality educational products that aim to improve students' critical thinking skills. The focus of this study is on the final stage of product development and includes recommendations for future research using educational or experimental methods. The qualitative descriptive analysis approach used in this study highlights the potential of the textbook to enrich teaching materials, broaden horizons, and increase students' sociocultural awareness. This study examines the effectiveness of the 4-D development model in creating an educational product that integrates case study-based learning strategies to enhance critical thinking skills and provide a valuable resource for instructors and students in business education courses.